Industrial engineering as a bridge between campus and the world of work: An implementation study on engineering students - Rosnelli Rosnelli; Yuniarto Mudjisusatyo; Darwin Darwin (Institute of Information Technology and Social Science (IITSS), 2025)
The ever-evolving paradigm shift in higher education demands that engineering universities be able to integrate the academic world with the real needs of industry. This study aims to analyze the implementation of Industrial Engineering education as a bridging strategy between universities and the workforce in preparing competent, adaptive, and work-ready engineering students. The research employed a qualitative descriptive approach using in-depth interviews, observations, and document analysis involving lecturers, students, and industrial partners at a state university in western Indonesia. The findings reveal that Industrial Engineering-based learning fosters analytical thinking, collaborative skills, and a practical understanding of production systems and industrial management. Collaboration between academia and industry practitioners strengthens the link and match within the engineering curriculum and accelerates students' adaptation to professional work culture. Therefore, the implementation of Industrial Engineering serves as a strategic bridge between academia and industry to produce graduates who are relevant, innovative, and globally competitive.